Tissue Levels of CD80, CD163 and CD206 and Their Ratios in Periodontal and Peri-Implant Health and Disease. - Yilmaz, Mustafa; Demir, Esra; Firatli, Yigit; Firatli, Erhan; Gürsoy, Ulvi Kahraman (My University, 2022)
This study aimed to compare tissue levels of CD80 (pro-inflammatory macrophage-related surface marker), CD163, and CD206 (anti-inflammatory macrophage-related surface markers), and their ratios in periodontal and peri-implant health and disease. Altogether, 36 tissue samples were obtained from 36 participants with clinically healthy gingiva ( = 10), healthy peri-implant mucosa ( = 8), periodontitis lesions ( = 9), and peri-implantitis lesions ( = 9). CD80, CD163, and CD206 levels were assessed with immunoblotting. CD163 levels were found to be decreased ( = 0.004), and the CD80/CD163 ratio was found to be elevated ( = 0.002) in periodontitis lesions compared to healthy gingiva. Peri-implantitis lesions showed a tendency towards a higher CD80/CD163 ratio than in healthy peri-implant mucosa with a borderline difference ( = 0.054). No statistically significant difference was detected in CD80, CD163, and CD206 levels of periodontitis lesions when compared to peri-implantitis, and in healthy gingiva when compared to healthy peri-implant mucosa. A disruption in CD80/CD163 balance seems to be related to the pathogenesis of periodontitis and peri-implantitis, being less prominent in the latter. The reason behind this phenomenon may be either suppressed CD163 expression or reduced CD163+ anti-inflammatory macrophage abundance.
Keywords: macrophage; mannose receptor; peri-implantitis; periodontitis; scavenger receptor